Design and Devlopment of Taste Masked Orally Disintegrating Tablet of Aceclofenac - Hussain, Adil; Khinchi, M.P; Gupta, M.K.; Agrawal, Dilip; Sharma, Natasha (Asian Journal of Pharmaceutical Research and Development, 2013)
Orally disintegrating tablets are gaining popularity over conventional tablets due to Their convince in administration and suitability for patients. The purpose of this research was to mask the intensely bitter taste of aceclofenac and to prepare orally disintegrating tablets for achievement of quick onset of action of the drug. Aceclofenac is an analgesic which has been proved to be efficient in managing relief from pain and including pain after surgery. In the present study an attempt has been made to prepare bitterless orally disintegrating tablet of Aceclofenac using Eudragit E 100 as a taste masking agent. Mass extrusion was the technique used for preparing taste masked granules and tablet was prepared with using superdisintegrants like crospovidone, croscarmellose sodium and sodium starch glycolate, were prepared blend and evaluated for the pre-compression parameters such as bulk density, compressibility, angle of repose etc. The prepared batches of tablets were evaluated for hardness, weight variation, friability, drug content, disintegration time and in-vitro dissolution profile and found satisfactory. Among the formulations containing Crospovidone was least and tablets showed fastest disintegration. The drug release from orally disintegrating tablets increased with increasing concentration of superdisintegrants and was found to be highest with formulations containing Crospovidone. Thus results conclusively demonstrated successful masking of taste and fastest disintegration of the formulated tablets in oral cavity.